PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA FLIPBOOK DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA SEKOLAH DASAR - Febriana, Natasya; Indah Nurmahanani; Nurdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Good writing skills are essential in language learning, but students often have difficulty organizing ideas and conveying messages effectively. This research was motivated by the lack of student motivation in narrative essay writing skills. This research aims to improve narrative essay writing skills in class V students at SDN 1 Nagrikidul by applying a learning model Contextual Teaching and Learning with the help of Flipbook media. This type of research is classroom action research carried out on students. Data was collected by analyzing students' written texts, observations, field notes, and documentation. The research results show that using Flipbook media in the learning model Contextual Teaching and Learning can improve students' narrative essay writing skills. The average student writing skill score in the first cycle was 70.76 and increased to 91.92 in the second cycle. Apart from that, students' enthusiasm during learning also shows more active participation. This research concludes that the application of the model Contextual Teaching and Learning with flipbook media is effective in improving the writing skills of class V students. It is hoped that this research can be a reference for educators in implementing more innovative and interesting learning models and media in learning to write.